Effects of PEEP administration on arterial oxygenation under general anesthesia - Beştaş, Azize; Bayar, Mustafa Kemal; Erhan, Ömer Lütfi; Ezici, Musa; Avci, Levent (My University, 2002)
The main cause of deteriorated arterial oxygenation during general anesthesia is the formation of athelectasias. In this study, we examined the effects of PEEP administration on arterial oxygenation under general anesthesia. Twenty-four ASA I-II group adult patients, with no lung problems and no premedication undergoing abdominal surgery were included in the study. After 3 minutes of preoxygenation, thiopental (3 mg kg-1), vecuronium (0.08 mg kg-1) and fentanyl (3 ?g kg-1) were used for induction of anesthesia. Anesthesia was maintained with 50-50 % N2O/O2 and 1-2% sevoflurane. Patients were randomly allocated into 3 groups. Group I received no PEEP. 5 cmH2O PEEP was administered to Group II starting from 30th minute after induction, until the end of the surgery. 5 cmH2O PEEP was commenced to Group III 30 minutes after induction and PEEP was increased with 5 cmH2O increments at 5 minutes intervals until 15 cmH2O. PEEP was then reduced to 5 cmH2O with 5 cmH2O decrements at 5 minutes intervals. Hemodynamic parameters, peak and plateau airway pressures, compliance and arterial blood gas analysis were recorded before induction and at 15 minutes intervals after induction. Peak and plateau airway pressures, arterial oxygen pressure and oxygen saturations were significantly higher in Group III with respect to Group I without any important hemodynamic changes (p < 0.05). Increases in peak and plateau pressures, arterial oxygen pressure and saturation were not statistically significant in Group II. We concluded that a significant increase in PaO2 and SaO2 may be provided by application of higher PEEP levels during general anesthesia.
Keywords: Arterial oxygenation; General anesthesia; Positive end expiratory pressure